KECENDERUNGAN AGENDA PEMBERITAAN TRIBUN TIMUR TERKAIT ISU BUDAYA UANG PANAI - Muh. Medriansyah Putra Kartika; Turnomo Rahardjo (KAREBA : Jurnal Ilmu Komunikasi, 2021)
Indonesia is a country that has a variety of cultures. Various tribes in Indonesia still maintain their customs or habits, one of which is the custom of marriage. Marriage customs in Indonesia have their own processions and what is discussed this time is the Bugis-Makassar marriage custom known as the Panai Money. However, the phenomenon of panai money has now become a polemic among young people, especially since several media reported on marriages whose nominal bills are quite high, ranging from hundreds of millions to billions of rupiah. This study aims to find out and describe how the trend of the news agenda in Tribun-Timur is in reporting the culture of panai'. The method used is quantitative content analysis in order to analyze the tendency of the East Tribune in reporting the issue of panai culture which is analyzed based on the Agenda Setting Theory. The results of the research show that the Tribun-Timur reporting agenda on the issue of Uang Panai' culture mostly uses a straight news reporting style and tends to be informative and the tone of the news also tends to be positive.